Lymphoma: current status of clinical and preclinical imaging with radiolabeled antibodies - England, Christopher G. (Eur J Nucl Med Mol Imaging, 2016)
Lymphoma is a complex disease that arises from cells of the immune system with an intricate pathology. While lymphoma may be classified as Hodgkin or non-Hodgkin, each type of tumor is genetically and phenotypically different and highly invasive tissue biopsies are the only method to investigate these differences. Noninvasive imaging strategies, such as immunoPET, can provide a vital insight into disease staging, monitoring treatment response in patients, and dose planning in radioimmunotherapy. ImmunoPET imaging with radiolabeled antibody-based tracers may also assist physicians in optimizing treatment strategies and enhancing patient stratification. Currently, there are two common biomarkers for molecular imaging of lymphoma, CD20 and CD30, both of which have been considered for investigation in preclinical imaging studies. In this review, we examine the current status of both preclinical and clinical imaging of lymphoma using radiolabeled antibodies. Additionally, we briefly investigate the role of radiolabeled antibodies in lymphoma therapy. As radiolabeled antibodies play critical roles in both imaging and therapy of lymphoma, the development of novel antibodies and the discovery of new biomarkers may greatly affect lymphoma imaging and therapy in the future.